Towards Multifunctional Materials Incorporating Elastomers and Reversible Redox‐Active Fragments. Issue 48 (7th October 2014) - Tarrés, Màrius; Viñas, Clara; Cioran, Ana M.; Hänninen, Mikko M.; Sillanpää, Reijo; Teixidor, Francesc
Abstract This paper presents a novel and unique feature of metallacarboranes, consisting of the linkage of this redox electro‐active site to a stretchable polymer. This is based on polyTHF, a known and applied material. This hybrid material has the two ends functionalized: one with the aforementioned redox molecule and the other with a terminal OH group, both linked by a molecular spring. Moreover, the redox electro‐active molecules can be synthesized with either cobalt (cobaltabisdicarbollide) or with iron (ferrabisdicarbollide), species whose respective E1/2 value differs by almost 1 V. The polymerization mechanism, based on an intermediate molecular crystal structure, is explained through an unexpected cyclization process of the dioxanate derivative of the metallacarboranes with an additional THF molecule. This is achieved in the absence of any metal or external electrophile. Surface functionalization of a Pt electrode by the electropolymerization of pyrrole doped with the pristine metallacarboranes and with the polyTHF hybrid materials is reported in this paper.